OPTIMAL CRITERIA OF MULTIPARAMETER AEROCRETE PREPARATION PROCESS CONTROL - Zimovkin, V. V.; Kulinich, E. M. (Radio Electronics, Computer Science, Control, 2010)
The structure-algorithmic scheme of aerocrete preparation process control is proposed. Control is carried out using optimization criteria by the gradient method by a set of control and check signals and actuators. Results of multiparameter control system simulation and testing in the plant conditions are presented.